199k views
22 votes
Use a negative factor to factor the expression - 7a+49b - 35

1 Answer

3 votes

Answer:

using a negative facto to factor the expression will be:

- 7a+49b - 35 = -7(a-7b+5)

Explanation:

Given the expression

- 7a+49b - 35

Rewrite -35 as 5 · 7

Rewrite 49 as 7 · 7

so

= -7a + 7 · 7b - 5 · 7

as -7 is the common factor, so factoring out

= -7(a-7b+5)

Thus, using a negative facto to factor the expression will be:

- 7a+49b - 35 = -7(a-7b+5)

User Suvarna Pattayil
by
5.1k points